Palliative Care and Cardiovascular Disease and Stroke: A Policy Statement From the American Heart Association/American Stroke Association. Issue 11 (13th September 2016) - Braun, Lynne T.; Grady, Kathleen L.; Kutner, Jean S.; Adler, Eric; Berlinger, Nancy; Boss, Renee; Butler, Javed; Enguidanos, Susan; Friebert, Sarah; Gardner, Timothy J.; Higgins, Phil; Holloway, Robert; et al.
Abstract : The mission of the American Heart Association/American Stroke Association includes increasing access to high-quality, evidence-based care that improves patient outcomes such as health-related quality of life and is consistent with the patients' values, preferences, and goals. Awareness of and access to palliative care interventions align with the American Heart Association/American Stroke Association mission. The purposes of this policy statement are to provide background on the importance of palliative care as it pertains to patients with advanced cardiovascular disease and stroke and their families and to make recommendations for policy decisions. Palliative care, defined as patient- and family-centered care that optimizes health-related quality of life by anticipating, preventing, and treating suffering, should be integrated into the care of all patients with advanced cardiovascular disease and stroke early in the disease trajectory. Palliative care focuses on communication, shared decision making about treatment options, advance care planning, and attention to physical, emotional, spiritual, and psychological distress with inclusion of the patient's family and care system. Our policy recommendations address the following: reimbursement for comprehensive delivery of palliative care services for patients with advanced cardiovascular disease and stroke; strong payer-provider relationships that involve data sharing to identify patients in need of palliative care, identification of better care and payment models, and establishment of quality standards and outcome measurements; healthcare system policies for the provision of comprehensive palliative care services during hospitalization, including goals of care, treatment decisions, needs of family caregivers, and transition to other care settings; and health professional education in palliative care as part of licensure requirements.